THE EFFECT OF GREEN ACCOUNTING KNOWLEDGE, ENVIRONMENTAL AWARENESS AND GREEN MARKETING ON SUSTAINABLE CONSUMPTION - Setianingrum, Desi; Candra Sari, Ratna (Buletin Studi Ekonomi, 2024)
This study aims to determine the effect of (1) green accounting knowledge on sustainable consumption, (2) environmental awareness on sustainable consumption, and (3) green marketing on sustainable consumption. This study uses quantitative research. Its population comprises accounting students at Universitas Negeri Yogyakarta (UNY). The convenience sampling method is used to obtain 196 respondents. The data analysis technique used to test the hypotheses is multiple linear regression. The results of this study indicate that: (1) green accounting knowledge has a positive effect on the sustainable consumption of accounting students at UNY, indicated by a significance value of 0.000 < 0.05; (2) environmental awareness has a negative effect on the sustainable consumption of accounting students at UNY, indicated by a significance value of 1.161 > 0.05; and (3) green marketing has a positive effect on the sustainable consumption of accounting students at UNY, indicated by a significance value 0.000 < 0.05.